Endometrial Cancers Harboring Mutated Fibroblast Growth Factor Receptor 2 Protein Are Successfully Treated With a New Small Tyrosine Kinase Inhibitor in an Orthotopic Mouse Model. Issue 1 (1st January 2018) - Taurin, Sebastien; Yang, Chieh-Hsiang; Reyes, Maria; Cho, Sungpil; Coombs, Demetrius M.; Jarboe, Elke A.; Werner, Theresa L.; Peterson, C. Matthew; Janát-Amsbury, Margit M.
Abstract : Objectives: AL3818 (anlotinib) is a receptor tyrosine kinase inhibitor targeting vascular endothelial growth factor receptors (VEGFR1, VEGFR2/KDR, and VEGFR3), stem cell factor receptor (C-kit), platelet-derived growth factor (PDGFβ), and fibroblast growth factor receptors (FGFR1, FGFR2, and FGFR3). This study evaluates the efficacy of AL3818 studying tumor regression in an orthotopic murine endometrial cancer model. Methods: We tested the cytotoxicity of AL3818 on a panel of 7 human endometrial cancer cell lines expressing either wild-type or mutant FGFR2 and also assessed the in vivo antitumor efficacy in a murine, orthotopic AN3CA endometrial cancer model. AL3818 was administered daily per os either alone or in combination with carboplatin and paclitaxel, which represent the current standard of adjuvant care for endometrial cancer. Results: AL3818 significantly reduces AN3CA cell number in vitro, characterized by high expression of a mutated FGFR2 protein. Daily oral administration of AL3818 (5 mg/kg) resulted in a complete response in 55% of animals treated and in a reduced tumor volume, as well as decreased tumor weights of AN3CA tumors by 94% and 96%, respectively, following a 29-day treatment cycle. Whereas carboplatin and paclitaxel failed to alter tumor growth, the combination with AL3818 did not seem to exhibit a superior effect when compared with AL3818 treatment alone. Conclusions: AL3818 shows superior efficacy for the treatment of endometrial cancer irresponsive to conventional carboplatin and paclitaxel combination and warrants further investigation.